Metabolic profile of elite team handball - Póvoas, S. C.; Soares, J. M.; Rebelo A. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
This study analyzes the effect of an elite male handball game on blood and plasma metabolic markers. The anaerobic glycolytic metabolism seems to be moderately taxed during the match, although individual blood lactate values suggest that the glycolic rate is high in certain moments Fat metabolism seems to be strongly activated, particularly during 2nd half of the game, which may likely contribute to explain the reduced exercise intensity towards the end of the match.